Exploration of endogenous substrate cleavage by various forms of botulinum neurotoxins. (15th June 2015) - Guo, Jiubiao; Wang, Jinglin; Chan, Edward Waichi; Chen, Sheng
Abstract: Botulinum neurotoxins are the most potent protein neurotoxin known to human. The dual roles of BoNTs as both the causative agent of human botulism and a widely used protein-based therapeutic agent for treatment of numerous neuromuscular disorders/cosmetic uses make it an extremely hot topic of research. Biochemical characterization of these toxins was mainly confined to the recombinant light chains and substrate and little is known about their efficiency on the cleavage of endogenous substrates. In the present study, we showed that BoNTs exhibited variable activities on their endogenous substrates and that their efficiency to cleave recombinant and endogenous substrate was not consistent, presumably due to the differential recognition of their respective substrates in the natural SNARE complex format. Through testing the combinatorial effects of different BoNTs on cleavage of endogenous substrates, we showed that the combinations of LC/A and LC/B, as well as LC/A and LC/F, could enhance the activity of each individual BoNT. This finding may shed light on the future development of new BoNT serotypes for clinical application, and formulation of combinatorial uses of different BoNTs to minimize the development of immuno-resistance by using a lower amount of individual type. Highlights: BoNTs exhibited variable activities on their recombinant and endogenous substrates. Combinations of LC/A and LC/B, as well as LC/A and LC/F, could enhance the activity of each. Provides insights into development of new BoNT serotypes for clinical application. Provide solution to minimize the immuno-resistance issues of BoNT based therapies.